2007
DOI: 10.1002/art.22709
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of juvenile idiopathic arthritis in a multiethnic cohort: Ethnicity as a risk factor

Abstract: Objective. To study the influence of ethnicity on the risk of developing juvenile idiopathic arthritis (JIA) in a multiethnic community of patients with unrestricted access to health care.Methods. A questionnaire on ethnicity was distributed to all patients with JIA being followed up at the Conclusion. In this multiethnic cohort, European descent was associated with a significantly increased risk of developing JIA, and the distribution of JIA subtypes differed significantly across ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
151
6
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(187 citation statements)
references
References 17 publications
15
151
6
15
Order By: Relevance
“…It has been argued that the differences observed between geographic areas may reflect underrepresentation of milder forms of JIA, particularly oligoarthritis, because of referral bias, which could be attributed to restrictions in access to healthcare facilities. An indirect confirmation of this phenomenon was provided by an analysis of a multiethnic cohort in a large Western tertiary care hospital, which in contrast with some studies from India, did not find any difference in the percentage of patients with persistent oligoarthritis between patients of Indian subcontinent descent and either the total JIA cohort or the patients of European ancestry 7 . This limitation does not apply to the study by Fitzpatrick, et al, as nearly all their patients had access to health insurance.…”
Section: Rheumatologymentioning
confidence: 85%
See 2 more Smart Citations
“…It has been argued that the differences observed between geographic areas may reflect underrepresentation of milder forms of JIA, particularly oligoarthritis, because of referral bias, which could be attributed to restrictions in access to healthcare facilities. An indirect confirmation of this phenomenon was provided by an analysis of a multiethnic cohort in a large Western tertiary care hospital, which in contrast with some studies from India, did not find any difference in the percentage of patients with persistent oligoarthritis between patients of Indian subcontinent descent and either the total JIA cohort or the patients of European ancestry 7 . This limitation does not apply to the study by Fitzpatrick, et al, as nearly all their patients had access to health insurance.…”
Section: Rheumatologymentioning
confidence: 85%
“…Over the past 3 decades, several epidemiologic surveys have documented a remarkable, yet unexplained, disparity in the prevalence of JIA subtypes among different geographic areas or racial/ethnic groups 5,6,7,8,9,10,11,12,13 . In Western countries, the most common category is oligoarthritis, but this form is rare in India, New Zealand, The Middle East, and South Africa, where polyarthritis predominates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age at onset of JIA in the patients with uveitis was 3.2 years (range 0-14) ( Table 2). The mean age for developing uveitis was 5.2 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and the mean time interval between the onset of JIA and development of uveitis was 21.9 months (range À4 to 48), with one case developing uveitis 4 months before the onset of JIA. Oligoarticular onset, rheumatoid factor negativity (o14 IU ml À1 ) and low anti-cyclic citrullinated peptide (o4.5 U ml À1 ), as well as younger age at onset of JIA were all significantly associated with JIA accompanied by uveitis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…3,5 However, the contribution of each risk factor may also vary among ethnic groups, presumably because of variations in genetic background. 6 Human leukocyte antigen (HLA) typing is considered useful for assisting in the diagnosis of autoimmune disease-associated uveitis such as HLA-B27-associated uveitis. 7 It has also been reported that HLA-DRB1*13 is associated with susceptibility to JIA-associated uveitis in a Caucasoid population.…”
Section: Introductionmentioning
confidence: 99%